Pengetahuan dan Pemahaman Aturan Perpajakan, Kualitas Pelayanan dan Persepsi atas Efektivitas Sistem Perpajakan terhadap Kemauan Membayar Pajak dengan Kesadaran Membayar Pajak sebagai Variabel Intervening - Zainuddin, Zainuddin (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2018)
This research aimed to find factors that affect of awareness to pay taxes, tax paying knowledge and understanding of taxation laws, service quality and a good perception of the effectiveness of the tax system to taxpayers willingness to pay taxes, case study on individual taxpayers who perform as a freelancer that registered at KPP Pratama Ternate. Data was collected by using a random sampling toward 86 respondents. The data was analyzed by using the SPSS program to test whether the model used in this study quite appropriate as the model analyzed. Then the regression analysis was used to test the relationship between the variables above. The results of this research indicated that knowledge and understanding of taxation law, service quality, and a good perception of the effectiveness of the taxation system had a significant effect toward willingness to pay taxes. Also awareness to pay taxes had a significant effect toward willingness to pay taxes.